Mr. Fuzzbuster knows he's the favorite - McAnulty, Stacy (Two Lions, 2017)
Longtime pet cat Mr. Fuzzbuster knows that he is Lily's favorite, but with four new animals in the house, Mr. Fuzzbuster decides to show everyone who his young owner loves best.